HUBUNGAN ALAM DAN MANUSIA DALAM FILEM TOMBIRUO: PENUNGGU RIMBA (2017): RELATIONSHIP BETWEEN NATURE AND MAN IN TOMBIRUO: PENUNGGU RIMBA (2017) - Abdullah, Nur Afifah Vanitha; Muhd Shukri, Fatimah; Mohd Rosdi, Nur Aifaa Nabilah (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract ‘Tombirou: Penunggu Rimba’ (2017) (TPR) is a mystical action film based on the rural Sabahan community belief about nature. More than 99 per cent of this film was shot in forested areas, therefore relevant to the film’s ultimate idea, which is the importance of caring for nature and striking that balance between nature and man. The film also contains symbolism that conveys nature’s revenge against man for their irresponsibility. Thus, this paper studied the portrayal of man and nature in TPR. An approach was devised with content analysis as a tool to answer the said question. This was supported by applying Aldo Leopold’s ecocentrism (1949) to analyse the film. The primary research material was TPR, whilst additional data was retrieved from books, journal articles and newspaper articles. Findings showed that this film had portrayed the importance of preserving the balance between nature and man in life’s ecosystem. This factor is vital to ensure nature’s wellness and the balance between man and nature. The characters Tombiruo, Tobugi, Bobolian and Pondolou were also shown as agents of peace, mediators and caretakers of nature. Keywords: ecocentrism, Tombiruo: Penunggu Rimba, Malay film, film criticism, symbolism.